Pan con hierro heme: producción, composición centecimal, aceptabilidad y bioaccesibilidad In Vitro - Rengifo Silvano, Estefany Deyhanyra (2024)
The objective of the present study was to use microparticles coated with bovine blood (BB) as a source of heme iron in white bread. The microparticles were produced using citrus pectin through the ionic gelation method, and through electrostatic interaction they were coated with bovine blood proteins and subsequently with sodium alginate. Six bread treatments were considered: control bread, bread with ferrous fumarate and breads with 10%, 15%, 20% and 25% level of addition of alginate-coated bovine blood microparticles (MSBR). The panels were characterized physicochemically, and subjected to tests of acceptability, microbiological quality and iron bioaccessibility. The results indicate that the incorporation of microparticles coated with bovine blood did not modify the flavor profile of white bread. Likewise, the results show that iron levels in the panels gradually increase with increasing microparticle concentration. This indicates that the microparticles produced in the present study can be considered as a source of iron with the potential to be used in different food matrices.